Segmentasi Penjualan Obat Di Apotek Menggunakan Metode K-Means - Resty Awaliah Febrianty; Wina Witanti; Puspita Nurul Sabrina (Ikatan Ahli Informatika Indonesia, 2020)
Sales segmentation is the division of social structures into specific units that have the same characteristics and behavior. The purpose of segmentation is a more targeted sales process so that company resources can be used effectively and efficiently. Segmentation of drug sales can be said to be important because it can be used as supporting data to determine the availability of drugs that must be managed properly to ensure the needed drugs are always available. To determine sales segmentation, clustering is conducted. Clustering is a method in data mining, and is used to map data into smaller groups according to the similarity of each characteristic possessed. In doing the cluster process, the K-Means method is used. This method will classify the level of similarity by determining the number of groups formed and grouping is measured by the proximity of the object so that each group contains data that is similar to the mean value at the center of mass. The purpose of this study is to produce a system that can group drug sales data into four groups according to the time of sale of the drug. The four groups are taken from the calculation using the elbow method. Research on data mining to determine sales segmentation at the Anugrah Farma Padalarang pharmacy using a system built using the PHP programming language and MySQL database. The results of this data mining process can be used by the Pharmacy as a consideration in the process of supplying medicines at the Anugrah Farma Padalarang Pharmacy.Keywords: abstract keywords